2016
DOI: 10.5897/jpbcs2015.0551
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of resistance to rosette virus disease in groundnut (Arachis hypogaea L.)

Abstract: Groundnut rosette disease is one of the most damaging diseases militating against groundnut production in sub-Saharan Africa. The disease cause up to 100% yield loss whenever epidemic occurs. The most effective, economic and environmental friendly method to control the disease is through genetic resistance. Knowledge on inheritance of resistance to the rosette disease is required to accelerate breeding of resistant varieties. A study was conducted to understand the nature and magnitude of gene effect of resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The correlation of AUDPC for LLS and GRD with LLS and GRD severity was significantly positive as expected since LLS and GRD are epidemic diseases (Amoah et al, 2016). Orondo et al ( 2007) reported similar observations for AUDPC of groundnut groups Virginia, Valencia and Spanish for rosette and leaf spot resistance in Kenya.…”
Section: Discussionsupporting
confidence: 69%
“…The correlation of AUDPC for LLS and GRD with LLS and GRD severity was significantly positive as expected since LLS and GRD are epidemic diseases (Amoah et al, 2016). Orondo et al ( 2007) reported similar observations for AUDPC of groundnut groups Virginia, Valencia and Spanish for rosette and leaf spot resistance in Kenya.…”
Section: Discussionsupporting
confidence: 69%
“…In the test area, using the FAO 56 Penman Monteith equation (Eqn (1)) and daily meteorological data, the reference evapotranspiration (ET 0 ) was calculated in the test region. 35 The crop evapotranspiration (ET c ) was calculated using Eqn (2). When soil water content in the 0-20 cm layer is below 60% of the field moisture capacity, irrigation is conducted using Eqns (3) and ( 4), with supplementary irrigation every 7-10 days.…”
Section: Irrigation Levelsmentioning
confidence: 99%
“…where ET 0 is the reference evapotranspiration (mm day −1 ); R n is the net radiation (MJ m −2 day −1 ); G is the soil heat flux (MJ m −2 day −1 ); γ is the psychrometric constant (kPa °C−1 ); T is the mean air temperature at 2 m height (°C); u 2 is the wind speed at 2 m height (m s −1 ); e s is the saturation vapor pressure (kPa); e a is the actual vapor pressure (kPa) and Δ is the slope of the vapor pressure curve (kPa °C−1 ); ET c is the daily crop evapotranspiration (mm day −1 ); K c is the crop growth coefficient, exhibiting variability based on the growth stage (for sweet potato, this coefficient ranges from 0.65 to 1.16) 35 ; n is the number of days between irrigation events; ET m is the cumulative crop evapotranspiration during the monitoring period (mm); I is the irrigation amount (mm); and P is the effective precipitation (mm). Effective rainfall is defined as rainfall exceeding 5 mm within a 24-h period.…”
Section: Irrigation Levelsmentioning
confidence: 99%